Cow's Milk-related Symptom Score (CoMiSS) values in presumed healthy European infants aged 6-12 months: a cross-sectional study - Jankiewicz, Mateusz; Ahmed, Fatme; Bajerova, Katerina; Carvajal Roca, Maria Eva; Dupont, Christophe; Huysentruyt, Koen; Kuitunen, Mikael; Meyer, Rosan; Pancheva, Rouzha; Koninckx, Carmen Ribes; Salvatore, Silvia; Shamir, Raanan; et al. (European journal of pediatrics, 2024)
The Cow's Milk-related Symptom Score (CoMiSS) is an awareness tool for evaluating cow's milk-related symptoms. Previous studies have focused on providing CoMiSS values for healthy and symptomatic infants aged 0-6 months. However, there is a notable gap in the literature concerning CoMiSS values for infants older than 6 months. This cross-sectional study aimed to determine CoMiSS values in presumed healthy infants who have completed 6 months and are up to 12 months old, hereafter referred to as 6 to 12 months old. Physicians from six European countries prospectively determined CoMiSS values in infants attending well-child clinics. Exclusion criteria included preterm delivery, acute or chronic disease, and the consumption of a therapeutic formula, dietary supplements (except vitamins), or medication. The following information was collected: gestational age, gender, age, type of feed (breast milk or infant formula), and complementary feeding. Descriptive statistics were summarized with mean and standard deviation for normally distributed continuous variables, median and IQR for non-normally distributed variables, and differences in CoMiSS values were analyzed with appropriate tests. Data from 609 infants were obtained. The overall median (Q1-Q3) CoMiSS values were 3 (1-5). Significant differences were found across age groups (p < 0.001), but not across groups based on gender (p = 0.551) or feeding type (p = 0.880). Conclusions: This study provided CoMiSS values in presumed healthy infants aged 6-12 months. Additional studies should be conducted to establish the use of CoMiSS to assess cow's milk-related symptoms in infants 6 months and older. What is Known: • The Cow's Milk-related Symptom Score (CoMiSS) is an awareness tool for evaluating symptoms related to cow's milk. • CoMiSS values for presumed healthy infants aged 0-6 months infants are already available. What is New: • CoMiSS values in European infants aged 6-12 months are provided. • These CoMiSS values differed across various age groups but not across groups based on gender or feeding type.
Keywords: Cattle; Animals; skot; Female; Infant; novorozenec; ženské pohlaví; Allergens; průřezové studie; Infant Formula; mateřské mléko; lidé; Infant, Newborn; Milk; Milk, Human; Cross-Sectional Studies; kojenec; náhražky mateřského mléka; Milk Hypersensitivity; alergeny; zvířata; mléko; alergie na mléko; Humans